Impact of SMS Advertising on Purchase Intention for Young Consumers - Sanjoy Kumar Roy (International Journal of Financial, Accounting, and Management, 2023)
Purpose: It has been discovered that SMS advertising perception has a considerable direct or indirect impact on customer purchase intention. Based on the stimulus-organism-response (SOR) framework, this study focuses on providing an empirically supported response to this specific topic in the context of Bangladeshi university students after the COVID pandemic era. Methodology: The study employed a two-stage hybrid approach using structural equation modeling and artificial neural network modeling to assess and validate the findings. The study used convenience sampling and a structured questionnaire to gather data from undergraduate students. Results: The results indicate that SMS advertising perception significantly influences purchasing intention. Attitude toward SMS advertisement and advertising value also mediate the relationship. Conclusions: This study shows that SMS advertising perception influences purchase intention among Bangladeshi university students, with attitude and ad value mediating this effect. Using structural equation modeling and artificial neural networks, it provides insights for marketers in post-COVID mobile advertising. Future research should explore broader demographics and regions. Limitations: The research is limited to the Dhaka metropolitan area in Bangladesh, and customer experience may differ in other places. Future studies should concentrate on different geographic regions to explore the topic more. Only young customers were considered in this study; outcomes for other consumers may differ. Contributions: The study serves to broaden the area of research on SMS advertising perception, its impact on purchase intention in Bangladesh. Additionally, it helps marketers by encouraging better decision-making when developing successful marketing campaigns employing mobile-based SMS service advertisements after the pandemic epoch.